Guidance and Counseling in Inclusive Education: A Literature Study - Wasilatur Rahmah Siftia Rusydi; Reza Imtiyazul Fikri (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2025)
Education for all, or in popular terms, inclusive education, is one of the efforts made by the Indonesian government to realize the ideals of the nation. In the world of education itself, there are guidance and counseling services that help students to achieve their developmental tasks, which are, of course, in line with the concepts and goals of inclusive education. This literature study seeks to find common ground between guidance and counseling services in inclusive education, which sometimes overlap. From the analysis of several sources of articles, it can be concluded that guidance and counseling services play an important role in inclusive education; the provision of services is not much different from services in regular schools. All education systems, including guidance and counseling services, must adapt to the diversity of students. One way is to understand the characteristics of students, especially students with special needs.